Building collage with Ram Horn - Hodgell, Kris, artist (Colorado State University. Libraries, 2016)
CSU building collage with ram horn in the center.
CSU building collage of Old Main (black and white), the Oval (black and white), the Administration Building (color), 1960s Lory Student Center (black and white), 2016 Lory Student Center (color), 1960s Morgan Library (black and white), Artist's rendering of new stadium (color), Artist's rendering of Aggie Village Redevelopment.
Keywords: Story Map Introduction; Main Stage image; building collage; Ram Horn